Aesthetic anxiety - Johnson, Laurie Ruth (Rodopi, 2010)
Preliminary Material – Preface – Aesthetic Anxiety and the Uncanny – The Uncanny Before Freud: Psychological and Philosophical Aspects – Beautiful Breakdowns: Uncanny Symptoms and the Aestheticization of Illness – Conspiracy Theories: The Melancholy and Manipulated Male Subject – Too Much Memory: Uncanny Love – Conclusion - Childish Anxiety, Wish, Belief – Bibliography. Aesthetic Anxiety analyzes uncanny repetition in psychology, literature, philosophy, and film, and produces a new narrative about the centrality of aesthetics in modern subjectivity. The often horrible, but sometimes also enjoyable, experience of anxiety can be an aesthetic mode as well as a psychological state. Johnson’s elucidation of that state in texts by authors from Kant to Rilke demonstrates how estrangement can produce attachment, and repositions Romanticism as an engine of modernity
10.1163/9789042031142
Keywords: German literature; Uncanny; The (Psychoanalysis); Anxiety in literature; Anxiety; Aesthetics; German; Criticism; interpretation; etc